Pengaruh Pemberian Spelling Puzzle dengan Model Problem Based Learning terhadap Pencapaian Kompetensi Siswa IPA Kelas VII Materi Pemanasan Global dan Lapisan Bumi SMP Negeri 12 Padang - Eci Verwita Sari; Yurnetti Yurnetti (PILLAR OF PHYSICS EDUCATION, 2018)
Spelling puzzle is a simple instructional media that train thinking ability of students and improve social attitudes among learners. In using tools or instructional media needed a learning model that message to the students clearly. One of the science material of VII class Junior High School is global warming and the layers of the earth use many images in understanding the concept. Media spelling puzzle is an alternative media that can be used to understand the concept of the material. The research aimed to determine the effect of usage Spelling Puzzles with Problem Based Learning Model to Student Competency Achievement of Class VII Science on the material of global warming and layers of the earth state junior high school 12 padang. This type of research is quasi experiment with control group pretest-posttest design. The study population was all students of class VII SMP Negeri 12 Padang 2017/2018 school year. The sampling technique used was purposive sampling technique. Research data is the learning outcomes of learners on the competence of attitudes, knowledge, and skills. From the analysis of the data for the three competencies of students obtained the following results: 1) the average value of learning outcomes in competency attitude IPA has increased continuously, 2) the average value of the results of the pretest IPA at both 65 and 62.07 grade samples and results the second posttest grade sample of 82.76 and 75.86 for knowledge competence, 3) average value of science learning outcomes in both sample classes 84.90 and 80.79 for competency skills. From Uman Whitney test, obtained p> α so that the alternative hypothesis is accepted for knowledge competency, while for the skill competencies of Uman Whitney test, obtained p<α so that the alternative hypothesis is accepted.